Answer:
4x - 6 = -46
x = -10
Explanation:
We are given the following sentence equation into a mathematical equation and then solve it to find each number:
The difference between four times a number and six is –46.
Translating it in chunks to make it easier:
1) The difference between ---> means there is a subtraction sign
2) four times a number ---> assuming x to be the number ---> 4x
3) and six ---> 6
4) is -46 ---> = -46
Combining these to get:
![4x - 6 = -46](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k9uthfozjmqk54ogquxyrhrcdn97rawccj.png)
![4x = -46 + 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uvja0x1x60x337hx0v9qplsb18j7li9xl6.png)
![4x = -40](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vgjng6nhtqo5812ki5yjfb3nnfaq1de8jj.png)
![x=(-40)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zj9ndt5q9vk7460tef4vsfvzvbnl45blg0.png)
x = -10